1979
DOI: 10.1161/01.res.45.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolase activities in the rat aorta. III. Effects of regular swimming activity and its cessation.

Abstract: SUMMARY It is possible that one of the consequences of regular physical activity could be a change in vascular metabolism. We studied the effects of regular swimming activity on specific activities of aortic hydrolases of male rats. Enzymes included: neutral a-glucosidase and lysosomal /3-galactosidase, JV-acetyl-/}-glucosaminidase, cathepsin C, acid a-glucosidase, and acid cholesteryl esterase. After 8 or 16 weeks of a 1-hour/day swimming protocol, specific activities of four of the six aortic enzymes studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The fact that Group D running animals were significantly higher than the basal level indicates that running per se led to increases in aortic cholesterol. In contrast, Wolinsky et al (21) found that forced swimming (1 hr/day for 8 weeks) resulted in increased levels of an enzyme (acid cholesteryl esterase) involved in the catabolism of cholesterol by the aorta. This would seem to be contradictory to the present results.…”
Section: Discussionmentioning
confidence: 89%
“…The fact that Group D running animals were significantly higher than the basal level indicates that running per se led to increases in aortic cholesterol. In contrast, Wolinsky et al (21) found that forced swimming (1 hr/day for 8 weeks) resulted in increased levels of an enzyme (acid cholesteryl esterase) involved in the catabolism of cholesterol by the aorta. This would seem to be contradictory to the present results.…”
Section: Discussionmentioning
confidence: 89%
“…Aortic ACE activity is increased in rats on a chronic swimming regime, but liver and kidney acid lipase activities are unchanged (Wolinsky et al, 1979). Clearance of 125 I-labeled LDL from the circulation of these rats also does not differ from that of normal sedentary animals (Table 1; Wolinsky et al, 1980).…”
mentioning
confidence: 87%
“…Hypertension, for example, is a potent stimulus to acid esterase activity in the rat aorta, and the activity returns to normal when the animal is returned to a normotensive state (Wolinsky et al, 1978b). Unlike exercise, however, hypertension results in damage to the wall in association with these enzyme increases (Wolinsky et al, 1979). No information is yet available on LDL clearance in hypertensive humans or experimental animals.…”
mentioning
confidence: 99%